Distribution of hepatitis B virus genotypes and viral load levels in Brazilian chronically infected patients in São Paulo city Distribuição dos genótipos do vírus da hepatite B e níveis de carga viral em pacientes brasileiros cronicamente infectados na cidade de São Paulo - Rosana Alcalde; Fernando Lucas Melo; Anna Nishiya; Suzete Cleusa Ferreira; Mario Dante Langhi Júnior; Simone Sena Fernandes; Luis Augusto Marcondes; Alberto José Silva Duarte; Jorge Casseb (Revista do Instituto de Medicina Tropical de São Paulo, 2009)
The objective of the present study was to evaluate the serum viral load in chronically infected Hepatitis B virus (HBV) patients and to investigate the distribution of HBV genotypes in São Paulo city. Quantitative HBV-DNA assays and HBV genotyping have gained importance for predicting HBV disease progression, have been employed for assessing infectivity, for treatment monitoring and for detecting the emergence of drug resistance. Twenty-nine Brazilian patients with suspected chronic hepatitis B were studied, using real time PCR for viral load determination and direct DNA sequencing for the genotyping. The serology revealed chronic HBV infection in 22 samples. The HBV-DNA was positive in 68% samples (15/22). The phylogenetic analysis disclosed that eleven patients were infected with HBV genotype A, two with genotype F and two with genotype D. Thus, the genotype A was the most prevalent in our study. O objetivo do presente estudo foi avaliar a carga viral no soro de pacientes cronicamente infectados pelo vírus da Hepatite B (HBV) e investigar a distribuição de genótipos HBV na cidade de São Paulo. PCR quantitativo do HBV e genotipagem ganharam importância para a previsão de progressão da doença, empregada para avaliar a infectividade, para tratamento e acompanhamento e para detectar o aparecimento de resistência aos anti-retrovirais. Vinte e nove pacientes brasileiros com suspeita de hepatite B crônica foram estudados, utilizando PCR em tempo real para a determinação da carga viral e seqüenciamento direto para determinação do genótipo. A sorologia revelou que 22 estavam, de fato, cronicamente infectados pelo HBV. O HBV-DNA foi positivo em 68% das amostras (15/22). Em sete casos, HBV-DNA foi indetectável por PCR quantitativo. A análise filogenética mostra que onze pacientes foram infectados com hepatite B genótipo A, dois com genótipo F e dois com genótipo D. Desta forma, o genótipo A foi o mais prevalente em nosso estudo.